Mechanical analysis of skier activity in giant slalom - Jurij Hladnik; Radovan Dražumerič; Igor Petrović; Ivan Bon; Mateja Očić; Vjekoslav Cigrovski; Boris Jerman (PLoS ONE, 2026)
Propulsive mechanical work in alpine skiing can be performed by gravity and by the skier’s activity. In this study, the part of the work performed by the skier’s activity for the movement of the skier’s centre of mass (COM) relative to the skis (i.e., external skier activity mechanical work, W S A ) was analysed. The main objectives of the study were to determine (a) positive and negative W S A , (b) W S A performed in the skiing direction ( W S A , t ), and (c) mechanical work performed by individual external forces in giant slalom, including the corresponding power profiles. For this purpose, three-dimensional whole-body kinematics of five skilled skiers were measured with a global navigation satellite system and an inertial motion capture system, while skiing on a predefined giant slalom course. W S A was calculated upon a two-point skier model as the difference between the work performed by the ground reaction force (GRF) at the COM and at the midpoint between the ankle joints. The negative W S A was 3.1 times larger than the positive W S A , which answers an important question about the dominant muscle activity in alpine skiing. W S A , t was exclusively positive on the expense of negative W S A performed in other directions. W S A , t and its power are a characteristic of ski turn mechanics and only partly reflect the skier’s own propulsion. W S A , t presented 2.4%, gravity 93.1% and GRF 4.5% of the total positive work in the skiing direction, respectively. Regarding energy dissipation, 81.0% of the total negative work was dissipated in the ski-snow contact, 14.6% against the air drag and 4.4% was absorbed in the skiers’ bodies. Moreover, a new parameter for evaluation of skiing propulsion efficiency, considering also skier activity mechanical work, was defined.